1994
DOI: 10.1104/pp.104.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoplastic and Symplastic Peroxidase Activity from Norway Spruce by the Photooxidant Hydroxymethyl Hydroperoxide

Abstract: Young, clonal Norway spruce trees (Picea abies 1.) were exposed for 2 years at high altitudes to ambient atmospheric concentrations of photooxidants containing hydroxymethyl hydroperoxide (HMHP) as an important constituent. In spruce needles from a site with higher concentrations of organic peroxides in air, the apoplastic peroxidase activities were significantly lower than in needles exposed to lower organic peroxide concentrations. Cuaiacol peroxidase activities in total needle extracts were not affected. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…4, a and b). The presence of these isoperoxidases in apoplastic washing fluids of mature spruce needles has been reported previously (Polle and Chakrabarti, 1994;Polle and Junkermann, 1994).…”
Section: Resultsmentioning
confidence: 96%
“…4, a and b). The presence of these isoperoxidases in apoplastic washing fluids of mature spruce needles has been reported previously (Polle and Chakrabarti, 1994;Polle and Junkermann, 1994).…”
Section: Resultsmentioning
confidence: 96%
“…Whether or not peroxides taken up from the atmosphere may act toxic was discussed by Polle and Junkermann (1994). The authors concluded that organic peroxides such as hydroxymethyl hydroperoxide (HMHP) produced in the boundary layer and taken up by the plants may affect peroxidase activity in the apoplast.…”
Section: Resultsmentioning
confidence: 99%
“…They are strong oxidants like ozone, and have some toxic effects on plants by inactivation of enzymes, impairing metabolic processes, and blanching chlorophyll (Hewitt et al, 1990;Hewitt and Terry, 1992;Polle and Junkermann, 1994). Methyl hydroperoxide (CH 3 OOH), the most abundant organic hydroperoxide, has a longer lifetime of 2e3 days and is less soluble in water than hydrogen peroxide (H 2 O 2 ) (Cohan et al, 1999;Mari et al, 2000;Wang and Chen, 2006).…”
Section: Introductionmentioning
confidence: 97%